Minat terhadap Promosi Jabatan bagi Karyawan Milenial di Sektor Perbankan - Nurfitriani; Ulfa hidayati; Salahuddin Nur; Hanif Mutashim Billah (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – The purpose of this study is to analyze the effect of job promotion on the performance of millennial employees in the banking sector, particularly at Bank BRI KC Maros, and to understand the extent to which millennial employees interest in job promotion affects their motivation and performance in the work environment. Method – This study uses a quantitative approach with a simple linear regression analysis method. Data was collected through questionnaires distributed to employees of Bank BRI KC Maros, then processed using SPSS version 25 to test the validity, reliability, and influence between the variables of promotion and employee performance. Findings – The results of the study indicate that promotion does not have a significant effect on employee performance at Bank BRI KC Maros. These findings indicate that millennial employees continue to work with high dedication even without the prospect of promotion, reflecting their intrinsic motivation and professionalism in carrying out their duties. Practical implications – The practical implication of this study is that banking management needs to pay more attention to the intrinsic motivation and self-development factors of millennial employees, rather than focusing solely on job promotions as a form of reward. Training programs, flexible career development, and a work environment that supports work-life balance can improve the performance and loyalty of millennial employees. Originality/value – The original value of this research lies in its focus on the behavior and motivation of millennial employees in the Indonesian banking sector, which shows that performance is more influenced by intrinsic motivation than by opportunities for promotion.